Completion of Inheritance for Chinese Communities in the City of Medan - Merry Roseline Pasaribu (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Every human being strives for his life and his offspring to be in harmony and peace and to be able to maintain the life that has been obtained from the results of the struggle of his parents during his life, especially in maintaining the material and moral assets left by his parents during his lifetime. Marriage for the diverse Indonesian community results in the form and method of inheriting and the form of the system of inheritance differing from one another, in Chinese society the validity of marriage is in accordance with Article 1 paragraph 1 of the Marriage Law No. 1 of 1974, which is carried out based on religion and each other's beliefs, this is done by holding a paisin at the Temple and giving drinks to both parents and photos. This research is a sociological juridical research, namely how the implementation of legal regulations is applied in Chinese society, the data sources are primary and secondary obtained by means of interviews and observations. The results of the study that the heirs are sons, because sons have greater responsibility in the family while daughters do not become heirs and are only entitled to assets in the form of jewelery from their mothers, even if a family consists of several daughters then a daughter is chosen who is deemed capable of guarding the property until her granddaughter can inherit it again, if a dispute occurs it will be resolved by deliberation from the family with mediation carried out by the person who is considered the oldest in the family, if this is not successful then ask for help from the traditional elder. For Chinese people it is taboo and very embarrassing if there is a dispute over inheritance. Even then, if a family consists of several daughters, then the daughter is chosen who is considered capable of guarding the property, that is, until her granddaughter can be inherited again, if there is a dispute, it will be resolved by deliberation from the family with mediation carried out by the person who is considered the oldest in the family.